Brown Bowel Syndrome: A Multi-institutional Case Series. (June 2020) - Arnold, Christina A.; Burke, Allen P.; Calomeni, Edward; Mayer, Romana C.; Rishi, Arvind; Singhi, Aatur D.; Stashek, Kristen; Voltaggio, Lysandra; Tondon, Rashmi
Abstract : Brown bowel syndrome (BBS) is a rare condition associated with vitamin E deficiency and defined by prominent lipofuscin deposition in the muscularis propria. Eight unique cases of BBS were identified: 5 men and 3 women (mean age=58.6 y). Pertinent comorbidities included bariatric surgery=2, malnourishment=2, Crohn=2, cystic fibrosis=1, alcohol and cocaine abuse=1, and prior small bowel resections=1. Presenting symptoms included abdominal pain=3, bleeding=1, nausea and vomiting=1, and nonresponsiveness=1. Imaging studies were often abnormal: thickened bowel wall=3 (1 with a mass), small bowel obstruction=2, and edematous and dilated bowel wall=2. Most specimens were surgical resections (n=7, autopsy=1): extended right colectomy=2, small bowel only=5 (terminal ileum=3, jejunum=2). Two specimens were grossly described as mahogany, and 1 case contained a perforation. Histologic sections of all cases showed finely granular, brown cytoplasmic pigment in smooth muscle cells on hematoxylin and eosin. This pigment was most conspicuous in the muscularis propria (small bowel>colon), and it was not identified in the mucosa. The pigment was reactive with Fontana-Masson, carbol lipofuscin, Periodic acid-Schiff, and Periodic acid-Schiff with diastase, and electron microscopy was compatible with lipofuscin. The mean clinical follow-up was 208 weeks: 1 patient died of complications of encephalitis, the others were alive and well. BBS is important to recognize because it is linked with malnutrition, specifically vitamin E deficiency, and it can (rarely) clinically simulate malignancy. The diagnosis is based on the identification of the lipofuscin pigment in the cytoplasm of smooth muscle cells, which is most easily seen in the muscularis propria of the small bowel.